Surgical congenital anomalies in Albania: incidence, prenatal diagnosis and outcome - Ilirjana Bakalli; Elmira Kola; Robert Lluka; Ermela Celaj; Durim Sala; Inva Gjeta; Sashenka Sallabanda; Dea Klironomi (BMJ Publishing Group, 2019)
Introduction Significant progress has been made in the diagnosis and management of congenital anomalies (CA). In our study, we aimed to evaluate prenatal diagnosis, trend of surgical CA, mortality rate and the factors affecting their prognosis in our country.Methods We enrolled in our study all children with CA who underwent surgery from January 2008 to December 2017. We compared prenatal diagnosis, incidence and mortality for two 5-year periods: the first period in 2008-2012 and the second period in 2013-2017.Results During the study period, a total of 321 cases with CA were presented, with an incidence of 0.69-1.18 per 1000 live births. Intestinal, anal and esophageal atresia remain the most important CAs (23%, 18% and 16%), followed by diaphragmatic hernia and gastroschisis (10% and 7%). Comparing the incidence for the two periods, we did not find statistical differences (p=0.73), but the mortality rate has been reduced from 31.4% during the first period to 24.6% during the second period (p=0.17). Prenatal diagnosis has increased: 28% in the second period compared with 10% in the first period (p<0.001), without significantly affecting the prognosis (p=0.09). Birth of premature babies resulted in a significantly negative predictive factor for the prognosis of these anomalies (p=0.0002).Conclusion Incidence of CA has not changed over the years in our country. Advances in intensive care, surgical techniques and parenteral nutrition made in recent years have significantly increased the survival of neonates born with surgical CA. Birth of premature babies was a significantly negative predictive factor for the prognosis of these anomalies.